Penerapan Algoritma C4.5 Untuk Memprediksi Besarnya Penggunaan Listrik Rumah Tangga di Kota Batam - Yulia Yulia; Nurul Azwanti (Ikatan Ahli Informatika Indonesia (IAII), 2018)
Electricity has been proven from the activities carried out by everyday people. The use of electricity ranging from household appliances such as refrigerator, fan, iron, mixer, rice cooker to communication tools such as mobile phones, laptops and various other electronic devices desperately need electrical energy. The use of electricity today is the only thing that matters in people's lives. Batam is one of the major cities in Indonesia. The densely populated areas in Batam are the Batam Center area. Population density will also require electrical energy to be very high. Company as energy provider in Batam city is PT PLN Batam (b'right). If the population is not wise in using electricity, of course, will greatly affect the depletion of energy preparation lstrik in Batam City itself. Therefore, techniques are needed to make predictions in the use of household appliances for the purpose of the government in list listing program. Techniques in making predictions can use data mining techniques by classifying data using C4.5 algorithm. Results from calculation Algorithm C4.5 Formation of decision tree where variable number of family members, Building area and length of time at home. Testing done with Weka has produced the same rule from the result tree that formed.